Mesoporous silica MCM-48 molecular sieve modified with SnCl2 in alkaline medium for selective oxidation of alcohol - Endud, Salasiah (Elsevier Ltd., 2007)

(untitled)
Tin modified mesoporous silica MCM-48 with various Si/Sn ratios were synthesized under alkaline media by post-synthesis modification using rice husk ash as Si precursor and SnCl2 as tin source. Physicochemical information of the materials was obtained by XRD, N2-physisorption, FESEM, UV-VIS diffuse reflectance and FTIR spectroscopies. The tin modified MCM-48 samples were selective in the oxidation of benzyl alcohol to benzaldehyde by using tert-butyl hydroperoxide aqueous solution as oxidant. The catalytic activity can be correlated with the strong Lewis acidity generated by the presence of tin species in Si-MCM-48. The re-usability of tin modified MCM-48 catalysts and the effect of substrate to oxidant ratio on the catalytic activity are discussed.